Beyond episodic remembering: elaborative retrieval of lifetime periods in young and older adults. Issue 1 (2nd January 2020) - Acevedo-Molina, Mónica C.; Matijevic, Stephanie; Grilli, Matthew D.
ABSTRACT: Relative to young adults, cognitively normal older adults commonly generate more semantic details and fewer episodic details in their descriptions of unique life events. It remains unclear whether this reflects a specific change to episodic memory or a broader alteration to autobiographical narration. To explore age differences across different types of autobiographical narration, we created a lifetime period narrative task that involves describing extended events. For comparison, participants also described unique life events. All autobiographical narratives were scored for episodic, semantic, and other detail generation. Relative to young adults, older adults generated more detailed narratives for remote and recent lifetime periods, which was driven by their increased retrieval of personal and general semantic details. Older adults also generated more semantic details for unique life event narratives, along with reduced episodic detail. More broadly, in both groups lifetime period narratives were largely based on semantic details, whereas episodic details were more prominent in the descriptions of unique life events. These findings indicate that the elevated generation of semantic details associated with normal cognitive aging is reflected in multiple types of autobiographical narration. We suggest that lifetime period narration is a spared aspect of autobiographical memory among older adults.